Odpowiedzi

2009-12-09T18:18:26+01:00
7x + 14y= -35 / :7
-5x + 5y = -32 / ×(-1)

x + 2y= -35
5x - 5y = 32

x= -35 - 2y
5 × (-35 -2y) = 32

x= -35 -2y
-175 -2y = 32

x=-35 -2y
-2y =32 +175

x= -35 -2y
-2y= 207 / : (-2)

x= -35 -2y
y= -103,5

x= -35 - 2× (-103,5)
y= -103,5

x= -242
y= -103,5




2009-12-09T18:24:52+01:00
7x + 14y= -35 wyznaczamy x
-5x + 5y = -32
7x = - 35 - 14y
x = -(35 + 14y)/7
5(35 + 14y)/7 + 5y = - 32
5(35 + 14y) + 35y = - 224
175 + 70y + 35y = - 224
105y = - 224 - 175
105y = - 399
y = - 399/105
7x + 14y = - 35
7x - 14( - 399/105) = - 35
7x + 5586/105 = - 35
735x + 5586 = - 3675
735x = - 3675 - 5586
7x = - 9261
x = - 9261/7 = - 1323
y = - 399/105 = - 3,8